Effects of Seed Treatment on Seed Quality and Storability In Wheat (Triticum Aestivum L.) In North Western Himalayas (Bangladesh Journal of Botany, 2022)
Storage experiment was conducted to study effects of polymer, fungicides and insecticide on seed quality parameters and storability in wheat. Experimental material consisted of carry over wheat seeds (variety HPW-155) of rabi 2017 - 18. Different parameters namely, germination, seedling length, dry weight, vigour index - I, vigour - II, speed of germination, field emergence, 100-seed weight for 12 months of storage were recorded bimonthly. All parameters were found to decrease with the advancement in storage period. Results showed that seeds treated with polymer + vitavax 200 @ 2 g/kg of seed recorded higher germination percentage (95.00), seedling length (17.58 cm), seedling dry weight (0.0138 g), vigour index - I (1670) and vigour - II (1.311), speed of germination (19.98), 100-seed weight (5.54 g). Field emergence (87.33) were at par with vitavax 200 @ 2 g/kg of seed over untreated control. For the purpose of maintaing seed quality and enhancing storability, seed of wheat can either be treated with polymer @ 3 ml/kg of seed + vitavax 200 @ 2 g/kg of seed or vitavax 200 @ 2 g/kg of seed.Bangladesh J. Bot. 51(1): 113-121, 2022 (March)